2017
DOI: 10.1007/s00438-017-1356-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of tyrosine kinases in anole lizard indicate the conserved tyrosine kinase repertoire in vertebrates

Abstract: The tyrosine kinases (TKs) play principal roles in regulation of multicellular aspects of the organism and are implicated in many cancer types and congenital disorders. The anole lizard has recently been introduced as a model organism for laboratory-based studies of organismal function and field studies of ecology and evolution. However, the TK family of anole lizard has not been systematically identified and characterized yet. In this study, we identified 82 TK-encoding genes in the anole lizard genome and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Simionato et al [25] reported that gene family size does not generally reflect the evolutionary diversity of gene families, such as the tyrosine kinase family and the basic helix-loop-helix family [25][26][27]. Therefore, we tried to explore the difference in the OR gene numbers between marine and terrestrial mammals resulting from gene-specific duplications or increased numbers of gene gains and losses.…”
Section: Or Gene Numbers Of Marine Mammals Are Significantly Lower Thmentioning
confidence: 99%
“…Simionato et al [25] reported that gene family size does not generally reflect the evolutionary diversity of gene families, such as the tyrosine kinase family and the basic helix-loop-helix family [25][26][27]. Therefore, we tried to explore the difference in the OR gene numbers between marine and terrestrial mammals resulting from gene-specific duplications or increased numbers of gene gains and losses.…”
Section: Or Gene Numbers Of Marine Mammals Are Significantly Lower Thmentioning
confidence: 99%
“…Generally, TKs are categorized into 30 subfamilies [ 10 , 11 , 33 ]. The multiformity of TKs is likely to imply the complicacy of the pTyr-based signaling system [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the highly conserved TK domains, TK proteins also contain various functional protein domains interacting with other components within signal transduction pathways [ 9 ]. Based on kinase domain sequence and protein secondary structure, TKs are generally grouped into 30 subfamilies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KCNMA1 is a pore forming α-subunit of the large-conductance calcium- and voltage-activated potassium channel linked to heightened proliferation and brain metastases [ 37 ]. NOK is a potent oncogene expressed in multiple cancers [ 38 ], which activates signaling pathways including MAPK and PI3K by phosphorylating them [ 39 ]. Clearly, all these genes are important and subject to complex regulation, among which are the “repressor” effects of SUMOylated PR-A.…”
Section: Discussionmentioning
confidence: 99%